High school musical - Ortega, Kenny; Efron, Zac; Hudgens, Vanessa, 1988-; Tisdale, Ashley, 1985-; Walt Disney Home Entertainment (Firm); Disney Channel (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
A popular high school basketball star and a shy, academically gifted newcomer secretly decide to audition for their school's musical, a decision that turns their world and their school upside down
Title from container
"Includes original & sing along versions"--Container insert
Special features: Learning the moves featurette led by director/choreographer Kenny Ortega; never-before-seen music video "I can't take my eyes off of you"; "We're all in this together" music video; behind-the-scenes featurette
Director of photography, Gordon C. Lonsdale; score, David Lawrence; editor, Seth Flaum
Zac Efron, Vanessa Anne Hudgens, Ashley Tisdale, Lucas Grabeel, Alyson Reed, Corbin Bleu, Monique Coleman, Bart Johnson, Olesya Rulin, Chris Warren Jr., Ryne Sanborn
Rating: TV-G
Keywords: Musicals -- Drama; High school students -- Drama; High school athletes -- Drama; High school student activities -- Drama; Musicals -- Drama; High school students -- United States -- Drama